Back to the Future: From Appendage Development Toward Future Human Hair Follicle Neogenesis - de Groot, Simon C.; Ulrich, Magda M. W.; Gho, Coen G.; Huisman, Margriet A. (Frontiers in Cell and Developmental Biology, 2021)
Hair disorders such as alopecia and hirsutism often impact the social and psychological well-being of an individual. This also holds true for patients with severe burns who have lost their hair follicles. Hair follicles stimulate proper wound healing and prevent scar formation; thus, hair follicle research can benefit numerous patients. Although hair development and hair disorders are intensively studied, human hair follicle development has not been fully elucidated. Research on human fetal material is often subject to restrictions, and thus development, disease, and wound healing studies remain largely dependent on time-consuming and costly animal studies. Although animal experiments have yielded considerable and useful information, it is increasingly recognized that significant differences exist between animal and human skin and that it is important to obtain meaningful human models. Human disease specific models could therefore play a key role in future therapy. To this end, hair organoids or hair-bearing skin-on-chip created from the patient’s own cells can be used. To create such a complex 3D structure, knowledge of hair genesis, i.e., the early developmental process, is indispensable. Thus, uncovering the mechanisms underlying how HF progenitor cells within human fetal skin form hair buds and subsequently hair follicles is of interest. Organoid studies have shown that nearly all organs can be recapitulated as mini-organs by mimicking embryonic conditions and utilizing the relevant morphogens and extracellular matrix proteins. Therefore, knowledge of the cellular and extracellular matrix proteins in the skin of human fetuses is critical to understand the evolution of epithelial tissues, including skin appendages. This review aims to provide an overview of our current understanding of the cellular changes occurring during human skin and hair follicle development. We further discuss the potential implementation of this knowledge in establishing a human in vitro model of a full skin substitute containing hair follicles and the subsequent translation to clinical use.